Implementasi Pembelajaran Berbasis Projek dalam Pembentukan Karakter Siswa SD IT Sekabupaten Aceh Tenggara - Hanum OK, Azizah; Al-Farabi, Mohammad; Sanjaya, Idwar (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This study aims to: 1) analyze the character of students in everyday life in SD IT throughout Southeast Aceh district. 2) analyzing the implementation of project-based learning in building the character of IT SD students in Southeast Aceh district. 3) analyzing the supporting and inhibiting factors of teachers in implementing project-based learning in order to shape the character of IT SD students in Southeast Aceh district. This research is a qualitative research that produces descriptive data. To examine the problems that have been formulated, literature study is used. The research data sources are in the upper groups: 1) The primary data in this study are data obtained from events in the research or from existing witnesses, such as interviews with school principals, teachers, and all relevant participants. 2) Secondary data in this study are documents, articles or relevant scientific work and others related to research. SDIT Aceh Tenggara District is diverse, some have good character such as honesty, discipline, courage, responsibility, and others, but there are also those who are not good, such as lying, lazy, and so on. 2) The implementation of Islamic Religious Education learning with the Project-Based Learning Model at SDIT Aceh Tenggara District is made up of several groups, usually 6 groups, but there can be less than 6 groups because it is adjusted to the number of students present when participating in Islamic Religious Education learning activities in class. So this makes students enjoy learning Islamic Religious Education, it can be seen that students have good motivation to learn in participating in debate activities even though some students are busy alone, some are playing alone, and so on, however, students and teachers remain enthusiastic in problem-based learning in the classroom. 3) Supporting factors in implementing project-based learning in building character at SDIT Aceh Tenggara include: a) Subject teachers who are professionals in their fields. b) There is student enthusiasm in participating in project-based learning, c) Positive student motivation, and adequate educational facilities. While the inhibiting factors include: a) Obstacles that arise from students are not many students who are able to think critically and do not dare to express their opinions. b) Teachers who do not understand the Project-Based Learning method. c) Lack of teacher motivation and enthusiasm in teaching, d) Lack of teacher ability to lead students to a problem. e) Barriers related to learning time.